Estimating the incidence of occupational asthma and rhinitis from laboratory animal allergens in the UK, 1999–2000. Issue 8 (25th July 2003) - Draper, A; Newman Taylor, A; Cullinan, P
Abstract : We report a survey of the number of persons handling laboratory animals in the UK in 1999–2000. This estimate has allowed us to calculate annual incidence rates of allergic asthma and rhinitis attributable to laboratory animals, insects, and birds using numerators derived from cases reported to a national surveillance scheme (SWORD). The number of exposed employees has almost halved since the early 1980s. From these data, the estimated annual incidence rate of occupational asthma among persons working with small mammals is 1.56/1000 employees. Although reported cases are rare, estimated incidence rates of asthma attributable to birds (23.9/1000/year) and insects (2.35/1000/year) are high.